2021
DOI: 10.1038/s41536-021-00126-2
|View full text |Cite
|
Sign up to set email alerts
|

The common YAP activation mediates corneal epithelial regeneration and repair with different-sized wounds

Abstract: Regeneration/repair after injury can be endowed by adult stem cells (ASCs) or lineage restricted and even terminally differentiated cells. In corneal epithelium, regeneration after a large wound depends on ASCs (limbal epithelial stem cells, LESCs), whereas repair after a small wound is LESCs-independent. Here, using rat corneal epithelial wounds with different sizes, we show that YAP activation promotes the activation and expansion of LESCs after a large wound, as well as the reprogramming of local epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Cell proliferation is often regarded as a key element in wound closure. That said, we and others have previously reported that corneal wound closure occurs in a mater of days in mice 9 , 17 , 22 and in rabbits 50 , 51 , despite the fact that in mice, this phenomenon has been reported as being independent of cell proliferation induction 9 . Interestingly, our results from EdU labeling show that, unlike in mice, in zebrafish cell proliferation is induced quickly after wounding.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Cell proliferation is often regarded as a key element in wound closure. That said, we and others have previously reported that corneal wound closure occurs in a mater of days in mice 9 , 17 , 22 and in rabbits 50 , 51 , despite the fact that in mice, this phenomenon has been reported as being independent of cell proliferation induction 9 . Interestingly, our results from EdU labeling show that, unlike in mice, in zebrafish cell proliferation is induced quickly after wounding.…”
Section: Discussionmentioning
confidence: 74%
“…Some reports, however, have indicated potential in the central corneal cells to resolve epithelial injuries 18 and to replenish the stem cell pool after limbal injury 19 . More detailed analysis on corneal epithelial cell populations 20 , 21 , and the impact of the magnitude of the injury 22 , are providing new insigths in the mechanisms of corneal wound healing. An elegant study demonstrated that the dynamics of epithelial renewal are similar in zebrafish and mammalian cornea 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to self-renewal and stratification, wound healing represents one of the critical functions of healthy CE. In the case of minor wounds, the repair of surface CE is thought to be carried out without recruitment of LSCs, while excessive injuries require compensatory proliferation of LSCs and their transiently amplifying cell (TAC) progeny [ 2 , 32 ]. In many epithelial tissues including CE, nucleotide-induced increase of cytosolic calcium (Ca 2+ ) is known to act as the main initiator to the complex wound healing cascades [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…DIANA-TarBase and microT-CDS algorithms (genes union function) were used to identify experimentally supported and predicted miRNA/target-mRNA interactions, respectively, as well as significant KEGG pathways, in which target genes were involved ( Table 2 and Table 3 ). Among them emerged the ECM-receptor interaction and the focal adhesion pathways, already described in cornea homeostasis and normal physiological functions [ 27 ], corneal epithelial cell motility [ 28 ], neovascularization [ 29 ] and adhesion [ 30 , 31 ], the Hippo signaling pathway, playing a role in limbal cell proliferation, corneal wound healing and regeneration [ 32 , 33 ] and, as expected, the Neurotrophin signaling pathway. The latter was considered for more in-depth analysis: sixty and fifty genes, targeted by 18 and 16 out of 21 miRNAs (miR-337-5p, mir-34a-3p, mir-1227-3p did not show any target gene) were detected by DIANA-TarBase and microT-based analysis, respectively ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%